2020
DOI: 10.3390/f11020208
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Mechanisms of Foliage Recovery after Spring or Fall Crown Scorch in Young Longleaf Pine (Pinus palustris Mill.)

Abstract: We hypothesized that physiological and morphological responses to prescribed fire support the post-scorch foliage recovery and growth of young longleaf pine. Two studies conducted in central Louisiana identified three means of foliage regrowth after fire that included an increase in the gas exchange rate of surviving foliage for 3 to 4 months after fire. Saplings also exhibited crown developmental responses to repeated fire that reduced the risk of future crown scorch. Starch reserves were a source of carbon f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Southern pines vary in their allocation to bark with longleaf allocating more early growth to bark than slash, loblolly, and (presumably) shortleaf pine (Jackson et al 1999). However, all southern pines eventually develop sufficiently thick bark to withstand surface fires with minimal impacts; some southern pines can also reflush following fires that kill needles (Sayer et al 2021). Another fire adaptation is the hastening of crown lifting to avoid foliage and bud damage from convective heating (McGuire et al 2021).…”
Section: Fire Dynamicsmentioning
confidence: 99%
“…Southern pines vary in their allocation to bark with longleaf allocating more early growth to bark than slash, loblolly, and (presumably) shortleaf pine (Jackson et al 1999). However, all southern pines eventually develop sufficiently thick bark to withstand surface fires with minimal impacts; some southern pines can also reflush following fires that kill needles (Sayer et al 2021). Another fire adaptation is the hastening of crown lifting to avoid foliage and bud damage from convective heating (McGuire et al 2021).…”
Section: Fire Dynamicsmentioning
confidence: 99%
“…3b,c ; Michaletz & Johnson, 2007 ; Hood et al ., 2018 ; Michaletz, 2018 ; BĂ€r et al ., 2019 ). Postfire environmental conditions and species‐specific traits determine whether resulting functional and growth limitations will lead to vegetation recovery or mortality (BĂ€r et al ., 2019 ; Sayer et al ., 2020 ; Hood, 2021 ; Ruswick et al ., 2021 ). For instance, traits such as water stress resistance are observed to differ between disturbance‐dependent and obligate sprouters in Mediterranean‐type climate regions (Pratt et al ., 2012 ), with implications for postfire community composition.…”
Section: Physiological Controls Of Fire Behavior and Effectsmentioning
confidence: 99%
“…3c ) as for mortality from drought and herbivory, where sufficiently high PLC or low NSC results in mortality. This is consistent with recent work linking mortality and recovery from low‐intensity fire to prefire water status (van Mantgem et al ., 2018 ; Partelli‐Feltrin et al ., 2020 ) and concentrations of NSC (Zhu et al ., 2012 ; Sayer et al ., 2020 ). In addition, smoldering consumption can impact water uptake directly through root loss (O'Brien et al ., 2010 ).…”
Section: Physiological Controls Of Fire Behavior and Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that growing season burns can inhibit root growth leading to speculation that dormant season burns are preferable for maintaining longleaf pine productivity (Sayer and Haywood, 2006). Growing season burns may also negatively affect non-structural carbohydrate stocks, which could further constrain recovery and productivity (Guo et al, 2004;Sayer et al, 2020). Such negative effects may be magnified in locations where fire has long-been excluded, as burning in stands with accumulated understory vegetation and duff can produce higher fire intensity (Menges and Deyrup, 2001), reduce non-structural carbohydrate reserves (Varner et al, 2009), and enhance post-fire physiological stress (O'Brien et al, 2010).…”
Section: Introductionmentioning
confidence: 99%